1997
DOI: 10.1016/s0014-5793(97)00345-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mutational analysis of peptidyl prolyl cis/trans isomerases: active sites of Escherichia coli trigger factor and human FKBP12

Abstract: A low degree of amino acid sequence similarity to FK506-binding proteins (FKBPs) has been obtained for the peptidyl prolyl cis/trans isomerase (PPIase) domain of E. coli trigger factor (TF) that was thought to be significant with regard to the enzymatic properties of the bacterial enzyme. We examined whether the alteration of a negatively charged side-chain at position 37 (FKBP numbering) and a phenylalanine at position 99, both highly conserved through both types of enzymes, leads to parallel effects on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 38 publications
5
73
1
Order By: Relevance
“…This TF variant may thus be deficient only in the correct binding of peptide substrate rather than in the PPIase activity itself. Our results are in agreement with earlier findings by Fischer and co-workers, who found that the exchange of Phe-233 to Tyr resulted in the loss of TF PPIase activity toward tetrapeptides in vitro (31). In addition, when the F233Y mutant was used to complement a ⌬tig strain, a reduced survival rate on plates after storage for 25 days at 6°C was observed as compared with wild type TF (32).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This TF variant may thus be deficient only in the correct binding of peptide substrate rather than in the PPIase activity itself. Our results are in agreement with earlier findings by Fischer and co-workers, who found that the exchange of Phe-233 to Tyr resulted in the loss of TF PPIase activity toward tetrapeptides in vitro (31). In addition, when the F233Y mutant was used to complement a ⌬tig strain, a reduced survival rate on plates after storage for 25 days at 6°C was observed as compared with wild type TF (32).…”
Section: Discussionsupporting
confidence: 93%
“…2A), even when added in a 20-fold higher concentration than wild type TF (data not shown). TF Y221F showed a residual activity of ϳ15% compared with wild type TF, whereas TF E178V was slightly more active than wild type TF, as observed earlier (31). Importantly, none of the TF variants was degraded by chymotrypsin during the assay as detected by Western blotting (data not shown).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…We then performed pulse-chase studies to examine the effect of TF overproduction on protein export in more detail. In these experiments HDB38 (HDB37 tigϪ) was transformed with pJH42 or a nearly identical plasmid (pHL22) encoding a TF mutant (F233Y) that has almost no peptidylprolyl-cis-isomerase activity (40). OmpA was exported very slowly over a 10-min period in cells that overproduced wildtype TF (Fig.…”
Section: Fig 2 Disruption Of Tig Enhances Bla Export In Srp-deficiementioning
confidence: 99%
“…Peptides were characterized by electrospray ionization-mass spectrometry. Recombinant human Cyp18, human FKBP12, and human Pin1 were prepared as described elsewhere (27,28). The catalytic subunit of bovine heart cAMP-dependent protein kinase (protein kinase A) was obtained from Roche (Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%